STUDI KOMPARASI JUMLAH PENJUALAN DAN HARGA KARKAS AYAM BROILER SEBELUM DAN SAAT COVID-19 DI PASAR RAKYAT KABUPATEN KEBUMEN (STUDI KASUS DI PASAR TUMENGGUNGAN) - Marzukoh, Robingatun; Muatip, Krismiwati; Djatmiko, Oentoeng Edi (ANGON: Journal of Animal Science and Technology, 2022)
Background. The research entitled "Comparative Study of Broiler Chicken Carcass Sales and Prices Before and During Covid-19 at the People's Market of Kebumen Regency (Case Study at Tumenggungan Market)" was carried out on March 15 - April 25, 2021, at Tumenggungan Market, Kebumen Regency. This study aims to determine the average number of sales and the average price of broiler carcasses before and during covid-19 and to determine the difference between the average number of sales and the average price of broiler carcasses before and during covid-19. Methods. The method used is a survey method, the determination of the sample area by purposive sampling by selecting market type A with the largest population of broiler carcass traders and obtained Tumenggungan market, Kebumen Regency with 38 respondents. The analytical method used is descriptive analysis and t-test. Results. The results showed that there was a decrease in the average number of broiler carcass sales and a change in broiler carcass prices before and during covid-19. The average number of broiler carcass sales before covid-19 was 27,2 kg/day and during Covid-19 it was 2,1 kg/day. The average price of broiler chicken carcasses before Covid-19 was IDR 31,500 and during covid-19 the price was in the range of IDR 30.000-IDR 32.000. Conclusion. The results of the t-test showed that there was a significant difference between the average number of sales and the average price of broiler carcasses before and during covid-19.